2022
DOI: 10.3389/fpls.2022.943662
|View full text |Cite
|
Sign up to set email alerts
|

Red and Blue Light Affect the Formation of Adventitious Roots of Tea Cuttings (Camellia sinensis) by Regulating Hormone Synthesis and Signal Transduction Pathways of Mature Leaves

Abstract: Light is an important environmental factor which affects plant growth, through changes of intensity and quality. In this study, monochromatic white (control), red (660 nm), and blue (430 nm) light-emitting diodes (LEDs) were used to treat tea short cuttings. The results showed the most adventitious roots in blue light treated tea cuttings, but the lowest roots in that treated by red light. In order to explore the molecular mechanism of light quality affecting adventitious root formation, we performed full-leng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…Difference in lower-case letters indicates significant difference at P < 0.05. Shen et al, 2022), and thus longer root under 3R1B in this study might be related to higher IAA accumulation in root. Therefore, the better root development of pepper seedlings exposed to 3R1B leads to faster acclimatization.…”
Section: Treatmentsmentioning
confidence: 49%
See 1 more Smart Citation
“…Difference in lower-case letters indicates significant difference at P < 0.05. Shen et al, 2022), and thus longer root under 3R1B in this study might be related to higher IAA accumulation in root. Therefore, the better root development of pepper seedlings exposed to 3R1B leads to faster acclimatization.…”
Section: Treatmentsmentioning
confidence: 49%
“…(2015) , this growth may be related to the ability of 3R1B treatment to induce the formation of endogenous GA, which is an important growth regulator involved in cell elongation. Furthermore, the increase in root length and formation of adventitious roots for pepper seedlings under 3R1B may be due to IAA levels, as this treatment promoted polar IAA transport from apical shoot to downward portion, which regulated by genes involved in auxin formation and signal transduction as well as auxin transportation ( Liu et al., 2011 ; Shen et al., 2022 ), and thus longer root under 3R1B in this study might be related to higher IAA accumulation in root. Therefore, the better root development of pepper seedlings exposed to 3R1B leads to faster acclimatization.…”
Section: Discussionmentioning
confidence: 66%
“…In contrast, red light (600–699 nm) can enhance photosynthesis, thus elevating the accumulation of carbohydrates (Yue et al., 2021). Additionally, red and blue lights encourage the lengthening and thickening of tea roots, respectively, while blue light can promote the formation of more adventitious roots by producing more phytohormones (Shen et al., 2022).…”
Section: Applications Of Metabolomics In Tea Studiesmentioning
confidence: 99%
“…For example, indole-3-carboxylic acid, ABA, trans-zeatin, and JA levels change during AR formation in tea. Moreover, a transcriptome analysis of ARs under different light treatments showed that differentially expressed genes (DEGs) were significantly enriched in the plant hormone synthesis and transduction-related pathway, including flavin monooxygenase ( YUC ) and auxin influx carrier ( AUX1 ) ( Shen et al., 2022 ). In apple rootstock, the levels of the endogenous phytohormones indole-3-acetic acid (IAA), zeatin riboside, JA, GA, and ABA in the process of AR formation were changed, and DEGs were shown to be considerably enriched in hormone signaling-related pathways ( Tahir et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%